Kepatuhan Konsumsi Tablet Zat Besi Berdasarkan Tingkat Pengetahuan Ibu Hamil - Fitriana Ikhtiarinawati Fajrin; Ayu Erisniwati (Jurnal Kesehatan, 2021)
One of the factors causing the high prevalence of anemia is the low compliance of pregnant women in consuming iron during pregnancy. The compliance of pregnant women in consuming iron during pregnancy cannot be separated from the level of knowledge that pregnant women have. This study aims to analyze the relationship between compliance with iron tablet consumption and the level of knowledge of pregnant women. This type of research is an analytical study with a survey method with a cross-sectional approach. The research was conducted on July 1-August 15, 2020, which was conducted at BPS Ernawati, Laren District, Lamongan Regency, with 21 respondents. The data collection technique used a questionnaire. Data analysis used fisher exact correlation test. Based on the results of the study, it showed that the majority had less knowledge about the importance of consuming iron tablets, namely as many as 10 respondents (47,6%). The majority of respondents did not comply with the consumption of iron tablets (57,1%). The majority of respondents with insufficient knowledge were not obedient, (38,1%), the majority of respondents with sufficient knowledge, were obedient as (19,1%), while the majority of respondents with high knowledge were obedient, (14,3%), and based on the statistical test results obtained p-value (0,033). This study concludes that there is a relationship between compliance with iron tablet consumption on the level of knowledge of pregnant women at BPS Diana Ernawati.